Effects of Rapana venosa meal‐supplemented diets on reproduction, histopathology and some blood parameters of rainbow trout (Oncorhynchus mykiss) broodstock. (26th May 2021) - Sahin, Tolga; Yılmaz, Sevdan; Gürkan, Mert; Ergün, Sebahattin
Abstract: The present study aimed to investigate the effects of partial replacement of fishmeal with Rapana venosa meal in diets for rainbow trout ( Oncorhynchus mykiss ) broodstock. The results were analysed on reproductive performance, egg fatty acid composition, serum biochemistry, antioxidant enzymes and histopathological and histomorphological changes of the experimental fish. For the trial, rainbow trout (331.04 ± 11.72 g) were fed diets incorporated with R. venosa (whelk) meal at 0 g/kg (CD), 50 g/kg (R5), 100 g/kg (R10) and 150 g/kg (R15) for 90 days. At the end, whelk meal did not have a significant effect on reproductive and blood serum parameters. However, it significantly affected the egg fatty acid composition, catalase activity and histological structure of the intestine, liver and muscle tissues of fish. Increased histopathological anomalies such as significant supranuclear lipid vacuolization, cytoplasmic vacuolization and fatty deposits were observed in tissues as whelk meal increased in the diet. A moderate lipidosis of the connective tissue between the muscle fibres was observed in group R15. Histomorphological measurements of the intestine, excluding the mean intestinal enterocyte length, were significantly affected by diets. To conclude, whelk meal can successfully replace fishmeal at 50 g/kg in young rainbow trout broodstock diets.